Answer: X=-3.
Anne was correct at fist, but likely didn’t solve the rest of the equation. The correct answer is X=-3, from 5(2x - 3)= 20x + 15, simplified by the distributive property going to 10x - 15 = 20x + 15. You then subtract +15 from the right side, or left side if you want to have a more positive answer, though it depends. That leaves you with 10x - 30 = 20x. You subtract 10x from itself and from 20x. Then you have -30 = 10x. You divide 10x by -30, and you get -3. Therefore, X = -3.
Explanation: